Assessing the Prevalence of Hard Ticks in Dairy Cattle Across Diverse Agro-Climatic Zones of Western Maharashtra - Harihar Belsare, Bhagyashree; Dhanaji Pawar, Prashant; Madhavrao Chigure, Gajanan; Patilba Mhase, Prashant; Ranjeet Mhaisekar, Nirja; Shrirang Dhaygude , Vitthal (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study investigated the prevalence of hard ticks infesting dairy cattle across four distinct agro-climatic zones in Western Maharashtra, India, shedding light on critical challenges in livestock management. From June to February, a thorough screening of 375 dairy cattle was conducted, with a meticulous collection of ticks from various regions of the body as well as from the surrounding environment. The findings revealed that out of 375, 200 animals were infested, indicating an alarming overall prevalence of 53.30%. Notably, calves under one year showed even greater susceptibility, with infestation rates soaring to 70.00%. Among different demographics, female cattle experienced higher infestation levels (54.60%; 160/293) compared to males (48.80%; 40/82). The prevalence in crossbred animals was 59.70% (12/206), non-descript breeds 45.70% (42/92), and in native breeds 45.50% (35/77). Cattle in poor body condition were disproportionately affected, exhibiting a striking 76.40% (81/106) infestation rate, in contrast to those in medium or good condition. Ticks favoured specific sites on the host, with the neck region (38.50%) and ears (15.50%) identified as the most common areas of infestation. This research underscores the urgent need for targeted control strategies to mitigate tick infestations in dairy cattle, particularly among vulnerable populations.
Keywords: Bhagyashree Harihar Belsare; Prashant Dhanaji Pawar; Gajanan Madhavrao Chigure; Prashant Patilba Mhase; Nirja Ranjeet Mhaisekar; Vitthal Shrirang Dhaygude